Character animation 2D skills for better 3D - Roberts, Steve 1941- (Focal Press, 2007)
An essential guide to the 2D animation skills required for professional 3D animation.
Print version record
Keywords: Animation (Cinematography) -- Handbooks, manuals, etc; Figure drawing -- Handbooks, manuals, etc; Computer animation -- Handbooks, manuals, etc; Animation (Cinéma); Guides, manuels, etc; Dessin de figures humaines; Guides, manuels, etc; Animation par ordinateur; Guides, manuels, etc; PHOTOGRAPHY; Techniques; Cinematography & Videography; ART; Film & Video; Animation (Cinematography); Computer animation; Figure drawing; handbooks; Handbooks and manuals; Guides et manuels